Visual pathology reports for communication of final margin status in laryngeal cancer surgery - Marina Aweeda; Carly Fassler; Alexander N. Perez; Alexis Miller; Kavita Prasad; Kayvon F. Sharif; James S. Lewis, Jr; Kim A. Ely; Mitra Mehrad; Sarah L. Rohde; Alexander J. Langerman; Kyle Mannion; et al. (Elsevier, 2024)
Background: Positive margins are frequently observed in total laryngectomy (TL) specimens. Effective communication of margin sampling sites and final margin status between surgeons and pathologists is crucial. In this study, we evaluate the utility of multimedia visual pathology reports to facilitate interdisciplinary discussion of margin status in laryngeal cancer surgery. Methods: Ex vivo laryngeal cancer surgical specimens were three-dimensional (3D) scanned before standard of care pathological analysis. Using computer-aided design software, the 3D model was annotated to reflect inking, sectioning, and margin sampling sites, generating a visual pathology report. These reports were distributed to head and neck surgeons and pathologists postoperatively. Results: Fifteen laryngeal cancer surgical specimens were 3D scanned and virtually annotated from January 2022 to December 2023. Most specimens (73.3%) were squamous cell carcinomas (SCCs). Among the cases, 26.7% had final positive surgical margins, whereas 13.3% had close margins, defined as <5 mm. The visual pathology report demonstrated sites of close or positive margins on the 3D specimens and was used to facilitate postoperative communication between surgeons and pathologists in 85.7% of these cases. Visual pathology reports were presented in multidisciplinary tumor board discussions (20%), email correspondences (13.3%), and teleconferences (6.7%), and were referenced in the final written pathology reports (26.7%). Conclusions: 3D scanning and virtual annotation of laryngeal cancer specimens for the creation of visual pathology reports is an innovative approach for postoperative pathology documentation, margin analysis, and surgeon-pathologist communication.